2022
DOI: 10.1007/s11831-022-09814-8
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Finite-Element Simulation of Fibre Metal Laminates

Abstract: Fibre metal laminates (FML) are layered materials consisting of both metal and reinforced composite layers. Due to numerous possibilities of configuration, constituent materials, etc., designing and testing such materials can be time- and cost-consuming. In addition to that, some parameters cannot be obtained directly from the experiment campaign. These problems are often overcome by using numerical simulation. In this article, the authors reviewed different approaches to finite element analysis of fibre metal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 91 publications
0
6
0
Order By: Relevance
“…FMLs can be modeled in micro, meso and macroscopic approaches in finite element analysis. [ 48 ] In this study, a finite element model was created in Hypermesh and solved using LS DYNA to analyze the deformation of laminate frustum with cut‐outs. In this regard, a coupon test on the aluminum, FRP material used for making frustum, was conducted by following ASTM E8, D7565 standard in universal testing machine.…”
Section: Resultsmentioning
confidence: 99%
“…FMLs can be modeled in micro, meso and macroscopic approaches in finite element analysis. [ 48 ] In this study, a finite element model was created in Hypermesh and solved using LS DYNA to analyze the deformation of laminate frustum with cut‐outs. In this regard, a coupon test on the aluminum, FRP material used for making frustum, was conducted by following ASTM E8, D7565 standard in universal testing machine.…”
Section: Resultsmentioning
confidence: 99%
“…15,16 Studies have shown that the damage types of FMLs include not only typical composite material damage modes such as fiber fracture, matrix cracking, fibers/matrix debonding and delamination, but also plastic deformation and fracture of metal, metal fiber interlayer debonding and other damage modes. 17,18 These damage modes do not occur independently but rather intersect and correlate with each other, progressively developing over time. This can be particularly serious at the edge of the hole, and the sequence and extent of these damages are critical in assessing the performance and service life of fiber metal laminates.…”
Section: Highlightsmentioning
confidence: 99%
“…The bridging effect between the metal and fiber layers and the anisotropy of the laminate make Glare laminates very different from traditional composites in terms of mechanical properties, and also lead to more complex damage behavior 15,16 . Studies have shown that the damage types of FMLs include not only typical composite material damage modes such as fiber fracture, matrix cracking, fibers/matrix debonding and delamination, but also plastic deformation and fracture of metal, metal fiber interlayer debonding and other damage modes 17,18 . These damage modes do not occur independently but rather intersect and correlate with each other, progressively developing over time.…”
Section: Introductionmentioning
confidence: 99%
“…The main industrially adopted FMLs are GLARE (glass laminate aluminum-reinforced epoxy), CARALL (carbon-reinforced aluminum laminate) and ARALL (aramid-reinforced aluminum laminate) [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. By using such hybrid components, positive hybrid effects can be achieved compared to when using pure fiber-reinforced plastics [ 16 , 17 , 18 ]. The improvement of the impact and crack resistance behavior and thus the improved damage tolerance of these hybrids is a good positive example [ 19 , 20 , 21 ] in addition to the improvement of the mechanical properties (static and dynamic), such as the increase in the stiffness, strength, fatigue strength [ 22 , 23 , 24 , 25 , 26 , 27 , 28 ] and damping, as well the electrical and magnetic properties [ 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%